2004
DOI: 10.21273/hortsci.39.5.1110
|View full text |Cite
|
Sign up to set email alerts
|

Blossom-end Rot Incidence of Tomato as Affected by Irrigation Quantity, Calcium Source, and Reduced Potassium

Abstract: `Equinox' tomatoes (Lycopersicon esculentum Mill.) were grown during the springs of 2001 and 2002 with black polyethylene-mulch and drip irrigation on an Arredondo fine sand in Gainesville, Fla., to study the influence of water quantity, Ca source, and reduced K on incidence of blossom-end rot (BER), marketable fruit yield, and fruit and leaf Ca concentration. Tensiometers were used to schedule irrigation in main plots when the soil matric potential reached 10 or 25 kPa. Subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“…Earlier studies have frequently observed that soil moisture stress can stimulate BER development (e.g. Adams and Ho, 1993), and reduced irrigation practices often result in a greater incidence of BER in tomatoes (Reid et al ., 1996; Franco et al ., 1999; Taylor et al ., 2004). It is well known that Ca movement in the plants and accumulation in the fruit are tightly linked with the transpiration rate of the plants (Keiser and Mullen, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies have frequently observed that soil moisture stress can stimulate BER development (e.g. Adams and Ho, 1993), and reduced irrigation practices often result in a greater incidence of BER in tomatoes (Reid et al ., 1996; Franco et al ., 1999; Taylor et al ., 2004). It is well known that Ca movement in the plants and accumulation in the fruit are tightly linked with the transpiration rate of the plants (Keiser and Mullen, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Ca movement in the plants and accumulation in the fruit are tightly linked with the transpiration rate of the plants (Keiser and Mullen, 1993). Basically, a decrease in plant transpiration rate could reduce plant total Ca uptake, and may thus increase BER occurrence in tomato (Taylor et al ., 2004) and sweet pepper (Tadesse et al ., 2001). However, as the leaf possesses a higher transpiration rate than the fruit, it often acts as a competing sink with the fruit for directional Ca flow and accumulation (McLaughlin and Wimmer, 1999; Taylor et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, excessive water supply leads to the spindling of tomatoes, limits the tomato physiological and reproductive growth, finally causes a low tomato yield [3940]. In addition, water supply has certain connections with the tomato BER i , while water whether to directly affect the BER i is still not fully understood [41]. Besides, under the condition of irrigation combined with mulching, soil salt was found to move towards the edge of the mulch, thus the salinity within the plant root-zone was decreased, which created a suitable environment for the growth of tomato [42].…”
Section: Introductionmentioning
confidence: 99%